(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2023)
Agroforestry systems (SAFs) can contribute to the recovery of degraded areas or to the restoration of fragmented landscapes, with emphasis on the diversification of species that can be produced simultaneously. The introduction of short-cycle crops in agroforestry systems, such as sweet potato (Ipomoea batatas (L.) Lam), is an affordable income option, as it demands low production costs and has a relatively short cycle. Sweet potato is a vegetable belonging to the Convolvulaceae family and is indicated for hot climates. In this sense, the present work aimed to evaluate the production of sweet potato in different agroforestry arrangements. The experiment was carried out at the Experimental Farm of the Federal University of Western Pará in Santarém, Pará. Sweet potato was introduced into agroforestry systems, with a completely randomized design and using three plots in each treatment (full sun, African mahogany and teak). The data showed that, under the conditions exposed by the research, sweet potato was not adapted to cultivation in shaded areas, presenting the highest production in full sun conditions, where the intercropping with forest species still does not generate shading for the cultivation.